The Financial Trilemma and Macroeconomic Instability: Empirical Evidence from Kenya - Njoroge, Lucas K. (American Journal of Trade and Policy, 2015)
The purpose of the study is to test whether the financial trilemma holds for a small open economy, and examine the implication of the implicit financial trilemma configuration on macroeconomic instability using Kenyan data. First, the study constructs the trilemma and macroeconomic instability indices and tests the financial trilemma. Second, the study empirically examines the effect of financial trilemma on macroeconomic instability. The results show that the financial trilemma does not hold for Kenya. However, by using the overall foreign participation to total equity turnover as a measure of financial openness, the trilemma indices are statistically significant. The results imply that the increasing financial openness is potentially driving the Kenyan economy towards financial trilemma characterized by a delicate balance of improving monetary independence and exchange rate stability. Financial openness is associated with increased macroeconomic instability. International reserve accumulation acts as a buffer and does not cause macroeconomic instability, implying that the Central Bank of Kenya conducted effective sterilization during the study period. This is the first study to test for the financial trilemma using Kenyan data. This study differs from other similar studies in a number of important ways. First, the study construct alternative financial trilemma indices that reflect the various reforms taking place in Kenya. Second, the study uses a unique data set based the newly released quarterly GDP data unlike most other studies that depend on annual data. JEL Classifications Code: F31